Funerary archaeology and changing identities : community practices in Roman-period Sardinia - Puddu, Mauro, (Archaeopress Roman archaeology., 2018)
This work analyses in detail the funerary evidence from burial sites in southern and central Sardinia, proposing an alternative interpretation of the island and of other Roman Provinces in which local communities played an active and creative role in shaping back the Roman-world within the specific material and historical conditions they lived in.